2017
DOI: 10.3310/hta21110
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital randomised assessment of a mechanical compression device in out-of-hospital cardiac arrest (PARAMEDIC): a pragmatic, cluster randomised trial and economic evaluation

Abstract: BackgroundMechanical chest compression devices may help to maintain high-quality cardiopulmonary resuscitation (CPR), but little evidence exists for their effectiveness. We evaluated whether or not the introduction of Lund University Cardiopulmonary Assistance System-2 (LUCAS-2; Jolife AB, Lund, Sweden) mechanical CPR into front-line emergency response vehicles would improve survival from out-of-hospital cardiac arrest (OHCA).ObjectiveEvaluation of the LUCAS-2 device as a routine ambulance service treatment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 82 publications
1
27
0
3
Order By: Relevance
“…Hallstrom and college reported in a multicenter, randomized trial of patients with OHCA (1,071 patients) that the use of an automated LDB‐CPR device was associated with poor neurological outcomes and a trend toward worse survival than manual CPR. More recently Gates et al failed to demonstrate a difference regarding clinical outcomes at 30 days between mechanical CPR using LUCAS‐2 device compared to manually compression in multicenter, randomized trials. These observations correspond to our results, that the LUCAS device showed no improvement in hospital survival by patients with OHCA.…”
Section: Discussionmentioning
confidence: 99%
“…Hallstrom and college reported in a multicenter, randomized trial of patients with OHCA (1,071 patients) that the use of an automated LDB‐CPR device was associated with poor neurological outcomes and a trend toward worse survival than manual CPR. More recently Gates et al failed to demonstrate a difference regarding clinical outcomes at 30 days between mechanical CPR using LUCAS‐2 device compared to manually compression in multicenter, randomized trials. These observations correspond to our results, that the LUCAS device showed no improvement in hospital survival by patients with OHCA.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in 4-h survival, and almost all the survivors in both groups (99% mechanical vs 94% manual) had good neurological outcomes by 6 months (8.5% mechanical vs 7.6% manual). PARAMEDIC 33,34 was another large trial. It was a pragmatic, clusterrandomized open-label trial, enrolling adults with outof-hospital cardiac arrest as the previous trials.…”
Section: Is the Automatic Cpr Effective?mentioning
confidence: 99%
“…7 Post-hoc additional analyses included reporting intensive care and hospital free days, mode of death and organ donation rates after death. HES admitted patient care data were used to calculate hospital length of stay and survival to hospital discharge, with supplementary discharge and death data collected in the trial.…”
Section: Methodsmentioning
confidence: 99%
“…The initial findings of the trial have been previously reported. 6,7 The study did not find an advantage to LUCAS chest compressions for the rate of return of spontaneous circulation, (LUCAS 32% vs control 31%, adjusted OR (adjusted odds ratio ((aOR)) 1.0 (95% confidence interval 0.9-1.1)), survived event (LUCAS 23% vs control 23%, aOR 1.0 (0.8-1.1)) or 30-day survival, (LUCAS 6% vs control 7%, aOR 0.9 (0.6-1.2)). However slightly more patients in the LUCAS arm had an unfavourable neurological outcome compared to those receiving manual chest compressions (5% vs 6% respectively, aOR 0.7 (0.5-1.0)).…”
Section: Introductionmentioning
confidence: 99%